IMPLEMENTASI, HAMBATAN DAN DAMPAK DISIPLIN APARATUR SIPIL NEGARA PADA BIRO SEKRETARIAT PIMPINAN BADAN PEMERIKSA KEUANGAN - Utama, Zahera Mega; Santika, Agnes Riris; Meirianita, Aldina; Armen , Muhammad Yudi (Jurnal Pijar, 2025)
Discipline is a fundamental aspect for employees in ensuring that a process is carried out accurately and in accordance with applicable rules and regulations. In the context of the civil apparatus in the Republic of Indonesia, this is regulated under Government Regulation (PP) Number 94 of 2021 concerning the Discipline of Civil Servants. This study was conducted with a sample of 51 employees to assess the extent to which the policy on employee discipline implementation within the Board Member Secretariat Bureau of the Audit Board of Indonesia (BPK) has been executed along with its impacts. The results indicate that, despite efforts to socialize the regulation in question, there are still civil apparatus (ASN) who do not fully understand the regulation and its consequences. In 2024, instances of ASN arriving late to work, unauthorized absences, and a lack of awareness among some ASN in fulfilling their duties and responsibilities were still found, which could potentially affect the achievement of planned performance targets. The method used in this study was qualitative analysis incorporating interviews, literature review, data analysis, and observation. The findings of this study are expected to provide input to relevant parties as supporting data for evaluating the implementation of employee discipline.